Desain Sistem Pemanenan Air Hujan untuk Mengurangi Defisit Air Bersih di Kota Bandung - Abdullah Syafe'i; Sulwan Permana; Adi Susetyaningsih (Institut Teknologi Garut, 2025)
Bandung City faces great challenges in meeting the demand for clean water due to rapid population growth and urbanization. This study aims to design a rainwater harvesting (RWH) system to reduce the water deficit. The method approach used includes hydrological analysis using the Mononobe method to calculate rainfall intensity, and the use of the Japanese Rational method to design the water storage system. The results showed that the RWH system is able to store 29,871.6 m³ of rainwater per year, which is equivalent to a 6.28% reduction in water deficit. The system has the potential to contribute significantly to water resource management and groundwater conservation in urban areas.